2009
DOI: 10.1097/gim.0b013e31818fa2ff
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations from the EGAPP Working Group: genetic testing strategies in newly diagnosed individuals with colorectal cancer aimed at reducing morbidity and mortality from Lynch syndrome in relatives

Abstract: CRC is a common disease responsible for an estimated 52,000 deaths in the United States in 2007. In about 3% of newly diagnosed CRC, the underlying cause is a mutation in a MMR gene (Lynch syndrome) that can be reliably identified with existing laboratory tests. Relatives inheriting the mutation have a high (about 45% by age 70) risk of developing CRC. Evidence suggests these relatives will often accept testing and increased surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
251
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 588 publications
(253 citation statements)
references
References 22 publications
2
251
0
Order By: Relevance
“…Specifically, we found that Health Heritage consistently outperformed Usual Care for all measures of family health history completeness and accuracy when both conditions were compared to the genetic assessment team. This is an important finding because it is important to compare to a gold standard (genetic assessment team) [6,30,][31]. In addition, our comparison showed that Health Heritage consistently performed at, or close to, the completeness of the family health history recorded by genetic counselors.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Specifically, we found that Health Heritage consistently outperformed Usual Care for all measures of family health history completeness and accuracy when both conditions were compared to the genetic assessment team. This is an important finding because it is important to compare to a gold standard (genetic assessment team) [6,30,][31]. In addition, our comparison showed that Health Heritage consistently performed at, or close to, the completeness of the family health history recorded by genetic counselors.…”
Section: Discussionmentioning
confidence: 70%
“…A family health history tool’s analytic validity needs to address how accurately the tool identifies disease in family members compared to a well-defined gold standard [30,31]. …”
Section: Introductionmentioning
confidence: 99%
“…Even for genomic applications currently in practice, we lack highly needed information on how validated genome technologies (such as HER2 testing) actually work in practice [32] and whether or not they lead to ‘real world’ net benefits in clinical outcomes. In fact, over the past 7 years, independent panels such as the U.S. Preventive Services Task Force and the EGAPP Working Group only made a few evidence-based recommendations for use of genomic applications in practice [33,34]. Two recent evidence reviews of promising genomics applications yielded inconclusive evidence of clinical utility for their use in practice [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…An alternate process to the family history first approach for LS identification is the tumour first approach with universal immunohistochemistry testing for the four MMR proteins, and/or microsatellite stability testing, in CRCs at time of initial surgery 27.…”
Section: Discussionmentioning
confidence: 99%